A Modelling and Simulation of a Sensorless Control of Five-phase PMSM Drives using Multi-dimension Space Vector Modulation - Kamel Saleh; Mark Sumner (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2016)
This paper is under in-depth investigation due to suspicion of possible plagiarism on a high similarity indexThis paper introduces a new method to track the saturation saliency for position measurement of a five-phase PMSM motor fed by a five-phase inverter through measuring the dynamic current response of the motor line currents due to the IGBT switching actions. The new method uses only the fundamental PWM waveform obtained using the multi-phase space vector pulse width modulation (i.e there is no modification to the operation of the five-phase inverter) similar to the fundamental PWM method proposed for a three-leg inverter. Simulation results are provided to verify the effectiveness of the proposed strategy for saliency tracking of a five-phase PMSM motor driven by five-phase inverter over a wide speed ranges under different load conditions.